PENGARUH MEDIA KARTU BERGAMBAR TERHADAP KEMAMPUAN BERBAHASA ANAK SPEECH DELAY - Hasmira; Endang Yunitasari, Septiyani (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Agama Islam Universitas Nahdlatul Ulama Purwokerto, 2024)
This study aims to analyze the effect of picture card media on the language development of children with speech delay. The research employs a quantitative approach with a pre-experimental design. Sampling technique used is purposive sampling to simplify the data collection and processing. The sample comprises 25 students with speech delay from RA Se-Kecamatan Bunyu, Tarakan City, North Kalimantan Province. In this study, the assessment of children's language development is conducted using the Denver Developmental Screening Test (DDST), commonly referred to as Denver II. This tool is designed to measure child development for individuals aged 0 to under 6 years. Denver II includes 125 test items categorized into four domains: personal-social, fine motor-adaptive, language, and gross motor. For this research, the focus is solely on the language domain, with modifications made to suit the specific conditions. A total of 26 statement items were included. The results indicate an improvement in Language Ability Scores: The Paired Sample T-test results show a significant difference between the pre-test score (mean 51.40) and the post-test score (mean 90.64). The increase in the mean score by 39.24 points signifies substantial progress in the language abilities of children with speech delay following the intervention using picture card media. Statistical Significance: The significance value (Sig. 2-tailed) of 0.000, which is less than 0.05, indicates that the difference between pre-test and post-test scores is statistically significant. This reinforces the conclusion that there is a positive change in the language abilities of children with speech delay. The limitations of this study include the relatively small sample size and the limited duration of the intervention. Future research with a larger sample size and a longer intervention period may provide a more comprehensive understanding of the impact of picture card media.